2018
DOI: 10.1101/410993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving The Performance Of The Amber Rna Force Field By Tuning The Hydrogen-Bonding Interactions

Abstract: # authors contributed equally * corresponding authors email: sponer@ncbr.muni.cz and pavel.banas@upol.cz KEYWORDS RNA, force field, MD simulation, enhanced sampling, folding, tetraloop.Recent studies generated large conformational ensembles of TNs 14-15, 17, 28-29, 31, 33-34 and TLs 14-15, 17, 28-29, 31, 35, 53-56 in order to assess the performance of RNA ffs. They showed that the available RNA ffs have persisting deficiencies causing, e.g., (i) shifts of the backbone dihedral angles to non-native values, (i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 110 publications
(172 reference statements)
1
37
0
Order By: Relevance
“…11 Subsequently, we have suggested its generalized interaction-specific variant (gHBfix) which represents a true extension of the parent ff. 12 We have demonstrated that boosting of all -NH…N-base-base interactions by 1.0 kcal/mol and destabilizing all sugarphosphate (SPh) H-bonds by 0.5 kcal/mol significantly improves simulations of RNA tetranucleotides and GNRA tetraloop without deteriorating simulations of other systems ( Figure 1). These parameters complement the common OL3 (ff99bsc0χOL3) [13][14][15][16] AMBER RNA ff version used together with modified phosphate van der Waals (vdW) parameters 17 and OPC water model.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…11 Subsequently, we have suggested its generalized interaction-specific variant (gHBfix) which represents a true extension of the parent ff. 12 We have demonstrated that boosting of all -NH…N-base-base interactions by 1.0 kcal/mol and destabilizing all sugarphosphate (SPh) H-bonds by 0.5 kcal/mol significantly improves simulations of RNA tetranucleotides and GNRA tetraloop without deteriorating simulations of other systems ( Figure 1). These parameters complement the common OL3 (ff99bsc0χOL3) [13][14][15][16] AMBER RNA ff version used together with modified phosphate van der Waals (vdW) parameters 17 and OPC water model.…”
Section: Introductionmentioning
confidence: 93%
“…12 is tuning H-bond interactions in order to: (i) support base -base interactions (left panel, blue dashed lines for -NH…N-interactions) and, simultaneously, (ii) destabilize SPh interactions (red dashed lines on the right panel); SPh interactions are those between 2'-OH groups and bridging (bO)/non-bridging (nbO) phosphate oxygens. The gHBfix potential is affecting all interactions of the same type while an analogous term can be used to modulate only structure-specific (individual) H-bonds (abbreviated as HBfix 10,12 ). In the present work, we suggest a variant separately targeting interactions involving terminal nucleotides (tHBfix term).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…60 This problem can be partly corrected, for example, by adding a specific term to stabilize the H-bonds. 98 Note that it does not mean that the H-bonding is uniformly underestimated in MD simulations of nucleic acids; there are other H-bonds which are over-stabilized by the force field, especially in RNA. 60,98 No means to enhance stability of the GG base pairing was used in this study.…”
Section: Force-field Approximations and Their Effect On G-stem Simulamentioning
confidence: 99%